Critical Reflection or Existential Trap: Are We Making Too Much of Scientific Rigor in a Dynamic Business World?. Issue 2 (19th June 2018) - Jones, Joseph A.; Miller, Ashley A.; Sarette, Michael J.; Johnson-Murray, Rachael M.; Alonso, Alex
Abstract : Ralph Waldo Emerson is known to have said, "the greatest wonder is that we can see these trees and not wonder more." As industrial and organizational (I-O) psychologists, we often encounter this very dilemma when we examine how numerous professions rise and fall in relevance. More recently, however, we have encountered this dilemma from an existential perspective as we strive to understand the evolution of our own profession and the situational characteristics making change inevitable. We have fallen into a trap—we, too, now look at all of our practices, aiming to reconfigure the makeup of our profession while losing sight of the macrotrends affecting more than just our evolved existence. Rather than focusing on the smaller issue first, we need to start by examining the broader issues affecting it.